Cultural Identity and Adaptation of Mainland Chinese Immigrants in Hong Kong. (May 2016) - Ngo, Hang-yue; Li, Hui
In this study, we develop a conceptual model to investigate how immigrants' cultural identity is related to their sociocultural adaptation and life satisfaction in the host society. In our model, we include two types of cultural identity (i.e., identity with the local society and with the home country), which are expected to have differential impacts on the outcome variables. We further propose that assimilation attitude and perception of discrimination serve as potential mediators in the above relationships. Several hypotheses are formulated and tested with a data set collected from a survey of 501 new immigrants from Mainland China to Hong Kong. The results of structural equation modeling indicate that local identity is positively related to assimilation attitude, which is then associated with sociocultural adaptation and life satisfaction of the respondents. Additionally, Mainland identity is found to be positively associated with immigrants' perceived discrimination, which is then negatively associated with their sociocultural adaptation and life satisfaction.